2006
DOI: 10.3201/eid1205.051060
|View full text |Cite
|
Sign up to set email alerts
|

Novel Swine Influenza Virus Subtype H3N1, United States

Abstract: A new subtype H3N1 may have arisen from reassortment of a H3N2 turkey isolate, a human H1N1 isolate, and currently circulating swine viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 40 publications
0
56
0
Order By: Relevance
“…Nevertheless, H3N1 viruses resulting from the reassortment between swine viruses (14,35,36) or from interspecies transmission and reassortment (2,37,38) have been detected previously. The HAs of the newly emerging H3N2 and H3N1 viruses that we describe are most genetically similar to those of recent human seasonal H3N2 strains from the 2010-2011 season, suggesting that these viruses evolved from a relatively recent spillover event of a human virus into pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, H3N1 viruses resulting from the reassortment between swine viruses (14,35,36) or from interspecies transmission and reassortment (2,37,38) have been detected previously. The HAs of the newly emerging H3N2 and H3N1 viruses that we describe are most genetically similar to those of recent human seasonal H3N2 strains from the 2010-2011 season, suggesting that these viruses evolved from a relatively recent spillover event of a human virus into pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Even though H3N1 viruses have previously been detected in U.S. swine, they are rare (2,14). The novel H3N1 viruses reported here have a unique combination of surface genes from contemporary human seasonal H3N2 hemagglutinin (HA) and classical swine H1N1 (cH1N1) neuraminidase (NA) and internal genes derived from H1N1pdm09 and hence are distinct from current swine H3 viruses circulating in the United States as well as the human seasonal H3 viruses circulating globally.…”
mentioning
confidence: 84%
“…Therefore, we have developed a new generation of LAIV for SIV. For this purpose, we chose an H3N2 virus, belonging to cluster III, which along with cluster IV, has been one of the most prevalent influenza viruses in American swine herds (19,20). By means of reverse genetics, this SIV was modified in the PB2 and PB1 genes, making it temperature sensitive.…”
mentioning
confidence: 99%
“…Three major lineages of SIV, including a classical swine H1N1 virus, an H3N2 subtype of human epidemic strain origin and an avian-like H1N1 swine influenza virus, have dominated in the pig population [1]. Genetic reassortments among those subtypes have resulted in generation of SIVs with several different genetic constellations [10,14,18]. It has been demonstrated that receptors for both human and avian influenza virus exist on the epithelial cells of the pig trachea [2].…”
mentioning
confidence: 99%